The personalised medicine: a paradigm of evidence-based medicine - Dhavendra Kumar (Istituto Superiore di Sanità, 2011)
The practice of "evidence-based medicine" aims at the conscientious, explicit and judicious use of the current best evidence in making decisions about the individualised patient care. The clinical genetics evolved from translational genetics research and contributes to the clinical care of patients and families through evidence-based health care in managing inherited disorders through accurate diagnosis, molecular pathology and assessing phenotypic correlations. Translational genetics and genomics research has led to the development of powerful tools for clinical diagnosis, assessing individual's genomic profile for disease prediction/prevention, high-throughput genome-wide screening for predisposition and/or protection to complex medical conditions, and discovery and development of new drugs and vaccines. Gene mapping and deciphering pathogenic mutations have helped in unravelling the basic biological mechanisms leading to new drug discovery and development. Targeted pharmacotherapy is now possible for managing the highly penetrant multi-system dominantly inherited conditions. Notable examples include rapamycin (sirolimus) in suppressing the mTOR pathway associated hamartomas in dominantly inherited cancer family syndromes and angiotensin converting enzyme receptor blockers (ACE-RB) in preventing aortic dilatation in Marfan syndrome and related familial arteriopathies. The translational genomic research is the essential prerequisite for developing sound evidence-based diagnostic, therapeutic and prognostic clinical protocols for the practice of personalised clinical medicine.